The Role Of Word-Of-Mouth As A Moderator In Influencing The Adoption Of Online Pharmacy In Saudi Arabia - Abdullah Ali A, Alsadoun (Pusat Pengajian Siswazah Perniagaan, 2022)
There is a low level of adoption and acceptance of online pharmacies in Saudi Arabia; only very limited Saudi Citizens are aware of the existence of online pharmacies and even fewer number of Saudis accessed and bought medicines using online pharmacy systems. Therefore, the online pharmacy business is facing a great challenge in adoption in Saudi Arabia; despite many attempts on using web applications that mimic the actual pharmacy operations; such attempts still preliminary and need more theoretical modelling and practical enhancements to trust, reliability, efficacy, and other factors of success.